Bloody technology: the sphygmograph in asylum practice. Issue 3 (September 2017) - Wallis, Jennifer
The sphygmograph, an instrument to measure and visually chart the pulse, was used by a number of asylum researchers in the late nineteenth century in an attempt to better understand mental disease. In charting the use of such a medical technology in the asylum, this article explores the utility of a practice-oriented approach in the history of psychiatry – as a window onto the alienist profession and as a means of investigating how new medical technologies were assimilated into everyday practice.